Assessing the Radial Effciency Performance of Bus Transport Sector Using Data Envelopment Analysis - Goyal, S. (CRC Press, 2021)
This study proposed an application of data envelopment analysis (DEA) to estimate the overall technical efficiency (OTE) for 52 bus depots of Rajasthan State Road Transport Corporation (RSRTC) for the financial year 2016-2017. The proposed study measures the efficiency and thoroughly explores the scope for optimal utilization of the input resources owned by depots of the RSRTC. The new slack model (NSM) of DEA is used as it calculates slacks for input and output variables. Also, this model satisfies the radial properties, unit invariance, and translation invariance. An input-oriented NSM model explicitly reduces input quantities (X) proportionally and renders no change in output level (Y). Four inputs have been considered, namely the number of buses, number of employees, total fuel consumption, and number of routes, and a single output, passenger kilometers occupied. The empirical results indicated that only 4 out of 52 depots are on the efficient frontier. All other depots possess the OTE value in the range of 0.7 to 1 relative to efficient depots. This study enables policy-makers to evaluate inputs for consistent output up to the optimum level and improve the performance of the inefficient depots. Â© 2022 selection and editorial matter, Vishal Jain, Sapna Juneja, Abhinav Juneja, and Ramani Kannan.